Microplastic Aerosol Contamination in Porto (Portugal) - Yuliya Logvina; Diogo Silva Moreira; Rui Pedro Moreira Santos; Inês Filipa Neves; Helena Ribeiro; Luís Pinto da Silva; Joaquim Esteves da Silva (Microplastics)
Microplastic pollution, particularly particles smaller than 5 mm, poses significant environmental and health risks due to their potential for inhalation and long-range transport. This study provides the first long-term assessment of airborne microplastics and fibers in Porto, Portugal, over 18 months (September 2022 to March 2024). Bi-weekly samples were collected using a Microplastic Collector NILU, which were size-fractionated into five categories (>125 μm, 125–63 μm, 63–25 μm, 25–12 μm, and 12–1.2 μm) and quantified via optical microscopy. Microplastic concentrations ranged from 26 to 1484 MPs/day/m2, while fiber concentrations varied from 14 to 646 fibers/day/m2. With a focus on the 12–1.2 μm size range due to their classifications as PM10 and PM2.5, the highest microplastic concentrations were 164 MPs/day/m2 (12–1.2 μm) and 534 MPs/day/m2 (25–12 μm). Recovery rates varied among polymers, with PP, PE-HD, and ABS showing high accuracy (75.9%) and PES significantly lower (26.5%). This study highlights the significant temporal variability in airborne microplastic and fiber pollution, correlations with meteorological parameters, and the need for ongoing monitoring and targeted mitigation strategies to address associated health risks.